Anogenital Lichen Sclerosus: Literature Review and 12-patient Clinical Series in Children - M.K. , Osminina; N.A. , Geppe; L.G., Khachatryan; M.D. , Velikoretskaya; O.V., Shpitonkova (International Journal of Psychosocial Rehabilitation, 2020)
Background and Objectives: Anogenital lichen sclerosus is of infrequent occurrence in children. The presented research is aimed at verifying clinical features and treatment approaches to anogenital lichen sclerosus in children and adolescents. Methods: We conducted a retrospective analysis of clinical presentations and treatment responses of 12 patients with anogenital lichen sclerosus; all stages of the study were retrospectively registered. Findings: 41% of the patients had extragenital morphea. 3 children were successfully treated with tacrolimus 0.03% ointment; due to the resistance to local steroid treatment, the others received systemic therapy with corticosteroids, penicillamine, or methotrexate; the remission was gained in all cases. Conclusions: Children with anogenital lichen sclerosus often have extragenital morphea backgrounded by immunological activity. The data suggest that step-changing therapy in anogenital lichen sclerosus should start with local topic steroids and tacrolimus ointment, followed by systemic immunosuppressive medications.